Pengaruh Tingkat Kesulitan Keuangan Perusahaan, Risiko Litigasi, Struktur Kepemilikan Manajerial dan Debt Convenant Terhadap Konservatisme Akuntansi ( studi empiris pada perusahaan manufaktur yang terdaftar di BEI ) - Yogi Ramadhoni; Zirman '; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was aimed to examine empirically: (1) the influence of a company’s financial distress to accounting conservatism, (2) the influence of litigation risks to accounting conservatism, (3) the influence of managerial ownership structure to accounting conservatism, (4) the influence of debt covenance to accounting conservatism. Independent variables used in this study are a company’s financial distress, litigation risks, managerial ownership structure, and debt covenance. The dependent variable used in this study is accounting conservatism that measured by Earnings/accrual measures model Givoly and Hayn.The population in this research includes companies listed in Indonesia Stock Exchange in the year 2009 to 2012. Samples in the research were selected by purposive sampling as many as 42 companies. Data analysis in this study uses regression analysis is basically the research of the dependence of the dependent variable (bound) with one or more independent variables (explanatory variables / bound).Based on the first hypothesis suggests that it is partially a significant difference between Conservatism in Financial Distress Manufacturing company. Under the second hypothesis suggests that it is partially a significant difference between the conservatism of Litigation Risk on Manufacturing company. Based on the third hypothesis suggests that it is partially a significant difference between the ownership structure manajeral against Conservatism in Manufacturing company. Based on the fourth hypothesis suggests that it is partially not a significant difference between the Debt Covenance against Conservatism in Manufacturing company.JOM Fekon Vol.1 No.2 Oktober 2014 Page 2Keywords : Financial Distres, Litigation Risk, managerial ownership structure, Debt Convenance